Influence of climate on the number of hospitalizations for nephrolithiasis in urban regions in Brazil - Abreu Júnior,João de (2020)
Abstract Introduction: Nephrolithiasis has a worldwide prevalence of approximately 5 to 15%, and its occurrence is associated with age, sex, race, dietary habits, geographic location, climatic conditions, and other factors. The objective of the present study was to determine the association between climate and the number of hospitalizations for nephrolithiasis (NH) in Brazilian cities located in different climatic regions. Methods: We analyzed data from cities with tropical and subtropical climates. The effects of the lowest (LT), mean (MT), and highest (HT) monthly temperatures and relative humidity of the air (RH) were assessed. Results: A positive association was found between the number of hospitalizations for nephrolithiasis and temperature ((LT x NH; R2=0.218; P<0.0001) (MT x NH; R2=0.284; P<0.0001) (HT x NH; R2=0.317; P<0.0001)), and a negative association was found between the number of hospitalizations for nephrolithiasis and the relative humidity (RH x NH; R2=0.234; P<0.0001). Interactions were also observed between MT and RH with respect to their effects on the NH, as described by a linear model (NH = 4.688 + 0.296 x MT - 0.088 x RH). The NH was higher in cities with tropical climates than in cities with subtropical climates (82.4 ± 10.0 vs 28.2 ± 1.6; P<0.00001). Conclusion: There is an association between the NH and variations in temperature and relative humidity.